Losses caused by gastrointestinal nematode infections in Dorper lambs under two nutritional status - Starling, Renan Zappavigna Costa [UNESP]; De Almeida, Fabiana Alves [UNESP]; Viana, Marcus Vinícius Gonçalves [UNESP]; De Castilhos, André Michel [UNESP]; Do Amarante, Alessandro Francisco Talamini [UNESP] (FapUNIFESP (SciELO), 2019)
The aim of this study was to evaluate the effect of two nutritional statuses on the productive performance of Dorper lambs naturally infected with gastrointestinal nematodes. Thirty-two lambs, grazing together on the same pasture, were allocated into four experimental groups: (G1) infected-supplemented diet, (G2) control-supplemented diet, (G3) infected-basal diet, and (G4) control-basal diet. Control animals received suppressive treatment with monepantel every two weeks, while precautionary anthelmintic treatments were given to all lambs of the infected groups with packed cell volume (PCV) <23%. There was reduction in the PCV means of all groups, which was more pronounced in the infected lambs that also presented reduction in total plasma protein values in comparison with the controls. Weight gain was affected by diet and infection status (P < 0.05). Daily body weight gain was 0.170 kg in the G1, 0.205 kg in the G2, 0.085 kg in the G3, and 0.116 kg in the G4. The cold carcass weight was 4.1% and 13.7% higher in controls in comparison with infected lambs, respectively, in the supplemented and basal diets. The infected groups, despite receiving precautionary anthelmintic treatments to prevent deaths due to haemonchosis, presented reduction in the production parameters in comparison with the controls.
Prejuízos causados pelas infecções por nematoides gastrintestinais em cordeiros Dorper submetidos a dois manejos nutricionais
Keywords: Haemonchus; Monepantel; Nutrition; Sheep; Trichostrongylus